The Battle for Rights – Getting Data Protection Cases to Court - Megan Richardson (Oslo Law Review)
Abstract This article compares the legal protection of privacy and personal data principally in common law jurisdictions. It points out that the growth of privacy law in these jurisdictions has traditionally centred on the ability of individuals to bring claims to court, with claims largely dealt with as a matter of common law (i.e. judge-made law). However, the absence of a generally accepted principle that individuals should be free to bring a claim in court for a breach of a statute has worked to limit the development of (statutory) data protection norms in the common law world. Nevertheless, the situation now appears to be changing with some recent cases.